Carboxymethyl chitosan-based coatings loaded with glutathione extend the shelf-life of harvested enoki mushrooms (Flammulina velutipes). (15th August 2022) - Li, Fuhou; Han, Qi; Wang, Weixia; Wu, Shengjun
Abstract: Carboxymethyl chitosan has anti-bacterial activity and good coating forming ability, and glutathione has antioxidant and browning-inhibiting capacity. This study investigated the effects of carboxymethyl chitosan-based coatings alone (1% carboxymethyl chitosan) or loaded with glutathione (1% carboxymethyl chitosan + 0.2% glutathione) on the refrigeration of harvested enoki mushrooms ( Flammulina velutipes ) for preservation. Compared with the control group, all the treated samples exhibited decreased total viable count, respiratory rate, weight loss and browning degree and increased soluble solid content and sensory overall likeness after 12 days of refrigeration ( P  < 0.05). Additionally, carboxymethyl chitosan-based coatings incorporated with glutathione were more efficient for the preservation of enoki mushrooms than carboxymethyl chitosan-based coatings alone. Therefore, treatment with carboxymethyl chitosan-based coatings could be a promising preservation method for harvested enoki mushrooms. Highlights: Chitosan coatings reduced total viable count in mushrooms. Chitosan coatings decreased respiratory rate and weight loss of mushrooms. Chitosan coatings increased soluble solid content in mushrooms. Chitosan inhibited browning in mushrooms. Chitosan coatings improved overall likeness of mushrooms.